USING YOUTUBE AS A LEARNING MEDIUM FOR EFL STUDENTS TO ENHANCE LISTENING AND SPEAKING SKILLS - Baroroh, Ummiyatul; Rizal, Daviq (Universitas Islam Sumatera Utara (UISU), 2023)
The purpose of this study was to investigate a method for integrating English foreign language learners with YouTube media to enhance listening and speaking skills. This analysis uses a qualitative method by adopting a survey research design. Data collection involved the distribution of questionnaires via Google Forms to English as a Foreign Language (EFL) students at both high school and university levels. The researchers aimed to investigate the acquisition of English, focusing on listening and speaking abilities, through the use of the YouTube app. A total of 79 respondents, comprising 23 men and 56 women, participated in this study. The research included an exploration of YouTube media as a tool for English language instruction to enhance listening and speaking skills. The procedures in this study include searching for data from online forms as well as various opinions from respondents which are useful for finding accurate research results. These findings are to be useful because they can give teachers and administrators a practical and theoretical understanding of undergraduate EFL learners perception of using YouTube as a supplemental resource for language acquisition.